Exploring Community Engagement Challenges in the Mining Sector of South Africa - Solomon Mandla Zembe; Neil Barnes (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
South Africa has recently experienced an increase in unrest within urban and rural communities, despite attempts from both government and business levels to engage communities through Community Engagement (CE) forums. This has had a negative impact on the operations of businesses in the mining industry in South Africa. Therefore, the purpose of this study was to explore CE challenges in the South African mining sector. The study used qualitative research methods where semi-structured interviews, and focus group discussion, were conducted among different stakeholders who were selected purposefully. The data were thematically analysed using the Atlas.ti software programme. The following themes were identified: Anglo Social Way, CE approaches, CE structures, guiding policies, terms of references, and municipality framework. It was recommended that community members needed to be educated on how the mine interacts with the community, its activities, and their participation as well as eliminating community unrest in order to improve communication amongst all stakeholders.